Sensory Denervation Modulates eIF-2 Alpha Kinase Expression in the Rabbit Lacrimal Gland - Nguyen, Doan H. (2006)
PURPOSE: To investigate the hypothesis that sensory denervation of the rabbit lacrimal gland results in dysregulation of protein synthesis. We used differential display of mRNA to identify genes associated with protein synthesis and secretion that may be altered in this situation. METHODS: New Zealand white rabbits underwent unilateral sensory denervation by the ablation of the trigeminal ganglion. After 7 days, the denervated and contralateral control lacrimal glands were removed. The effects of denervation on gene expression were carried out using differential mRNA display. Northern and Western blot analyses were used to verify differential gene expression. RESULTS: Differential mRNA display identified the gene heme-regulated inhibitor eukarytotic initiation factor-2 alpha kinase (HRI eIF-2α kinase) in the lacrimal gland, the expression of which was reduced in the denervated lacrimal gland. The sequenced fragment from differential display showed 94% identity to rabbit HRI eIF-2α kinase. The decreased expression of HRI eIF-2α kinase was confirmed by Northern and Western blots, and measurement of HRI eIF-2α kinase phosphorylation activity in the lacrimal gland after ablation of sensory neurons showed that it was significantly decreased compared with that of normal and control lacrimal glands. CONCLUSIONS: The results suggest that loss of sensory innervation has a role in the lacrimal gland, contributing to the expression of HRI eIF-2α kinase, a pivotal negative regulator of protein synthesis. A reduction in control of protein synthesis may lead to the translation of repressed messages associated with cell stress responses.